2006
DOI: 10.1002/pc.20159
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization compounding of HDPE/Kevlar composites. I. Morphology and mechanical properties

Abstract: The aim of this work is to perform the polymerization compounding to improve the properties of Kevlar/PE composites. The approach consists in involving the surface of a reinforcement in a polymerization process of a polymer to be used either as a matrix in the final composite or as a special surface treatment to enhance solid/polymer interface properties in the composite. The polymerization compounding process is illustrated here with the polyaramid fibers as reinforcements and polyethylene as a matrix. The nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…An evident alternative to eliminate all the aforementioned negative aspects is to perform the nanoparticle encapsulation as a gas–solid reaction, where the gaseous phase contains the monomer of interest. The polymerization of ethylene via Ziegler–Natta catalyst for nanoparticle encapsulation and composite preparation has been reported by several researchers,8, 15, 16 using a liquid suspension where the ethylene gas is dissolved. We also have successfully used this procedure to encapsulate zirconia nanoparticles in hexane 11.…”
Section: Introductionmentioning
confidence: 99%
“…An evident alternative to eliminate all the aforementioned negative aspects is to perform the nanoparticle encapsulation as a gas–solid reaction, where the gaseous phase contains the monomer of interest. The polymerization of ethylene via Ziegler–Natta catalyst for nanoparticle encapsulation and composite preparation has been reported by several researchers,8, 15, 16 using a liquid suspension where the ethylene gas is dissolved. We also have successfully used this procedure to encapsulate zirconia nanoparticles in hexane 11.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of composite materials depend on three main factors: the strength and elasticity of the reinforcing agent, the strength and stability of the matrix, and the quality of the interface between both elements to ensure optimum stress transfer . But highly polar and hydrophilic natural fibers are incompatible with most thermoplastic matrices (nonpolar and hydrophobic) . Nevertheless, this incompatibility can be improved by modifying the topology of the fibers via surface modification .…”
Section: Introductionmentioning
confidence: 99%
“…For example, AP-reinforced epoxy resin composites are an important class of tribological materials with good mechanical properties. [3] Yahaya [4] studied the mechanical properties of kenaf fiber and aramid fiber-reinforced epoxy composites and showed that aramid-reinforced epoxy resin has higher flexural and tensile properties than those of kenaf fiberreinforced composites.…”
Section: Introductionmentioning
confidence: 99%